The Queen of the Arctic: Louise Arner Boyd - Isaksson, Elisabeth; Ryall, Anka (Polar Research, 2023)
Louise Boyd (1887–1972) was a female pioneer in Arctic research whose legacy includes the exploration of north-east Greenland. In this Perspective piece, we use a broad interdisciplinary approach to investigate her career as a photographer and expedition leader. When documenting glacial retreat during the 1930s, she was at the forefront of the development of glaciology as a research discipline. Without family obligations and with seemingly inexhaustible financial resources, she used Arctic exploration to create an independent and self-defined life for herself.